Cyber-Physical System (CPS) Application- A REVIEW - Syarfa Najihah Raisin; Juliza Jamaludin; Fatinah Mohd Rahalim; Farah Aina Jamal Mohamad; Bushra Naeem (REKA ELKOMIKA: Jurnal Pengabdian kepada Masyarakat, 2020)
Due to its vast number of suitable applications, Cyber-Physical Systems (CPS) has been one of the emerging and rapidly-developed technologies in modern life. Its applications can be integrated and deployed in numerous sectors, for instance the automobile, home appliances, medical and industrial sectors. This field has seen immense development and research taking place, including the architecture model, security, communications mode, control systems model and also signal processing. CPS plays an important role in Industrial Revolution 4.0, where it is an integration of urbane network with intelligent production or process system. CPS main objective is to control the global networks with high credibility of data secured.  This paper is basically a review of the CPS architectures, characteristics and its applications in daily basis. This review paper discusses how CPS are implemented in various industries and how it improves the efficiency of a system or application. Additionally, security enhancements in certain aspects of CPS application will also be reviewed and addressed.